Biological Pathways and Biomarker Patterns in Autism Spectrum Disorder: Jalur Biologis dan Pola Biomarker pada Gangguan Spektrum Autisme - Tamarah H. Ahmed; Noor H. Al-Mousawi (Academia Open, 2026)
General Background Autism spectrum disorder is a complex neurodevelopmental condition characterized by marked heterogeneity in clinical presentation and underlying biology. Specific Background Increasing attention has been directed toward biological mechanisms such as immune dysregulation, oxidative stress, mitochondrial dysfunction, and neuroendocrine rhythm disturbances. Knowledge Gap Despite extensive research, findings remain fragmented across biological systems, limiting integrative understanding. Aims This article aims to synthesize current evidence on key biological pathways and biomarkers associated with autism spectrum disorder. Results The review identifies consistent abnormalities in inflammatory markers, oxidative stress indicators, mitochondrial function, melatonin regulation, and serotonergic activity, suggesting interconnected physiological alterations. Novelty The study offers an integrative synthesis that brings together immune, metabolic, and neurobiological evidence within a single analytical framework. Implications These findings support the relevance of multi-system biological perspectives in autism research and provide a consolidated foundation for future investigations into diagnostic and therapeutic strategies. Highlights: Multiple physiological systems show recurrent abnormalities in autism spectrum disorder. Immune and oxidative pathways appear closely interconnected across studies. Neuroendocrine rhythm disturbances emerge as a consistent biological feature. Keywords: Autism Spectrum Disorder, Neuroinflammation, Oxidative Stress, Biomarkers, Biological Mechanisms